Comparison between the Safety and Effectiveness of Al-Hijama (Cupping) and the Conventional Medical Therapy as Treatment for Sinusitis (II): Conventional Medical Therapy for Sinusitis - Eman A. Ghazy; Saad M. Al Muhayawi; Samiha A. Mourad (Journal of King Abdulaziz University: Medical Sciences, 2020)
Sinusitis has severe negative effects on the quality of life and on work productivity. Cupping (Al-Hijama in Arabic) is a historical, yet a successful, method of treatment for many health problems, and it is now an international evidence-based medical treatment. This study compared the effectiveness and the safety of the cupping therapy as an adjuvant or alternative to pharmacological therapy, based on clinical examinations and their corresponding laboratory results. A randomized and controlled clinical trial was conducted in the Prophetic Medicine Research Cupping Clinic of the King Abdulaziz University Hospital in Jeddah, Saudi Arabia, by recruiting 60 patients, who were suffering from chronic or recurrent acute sinusitis. The patients were divided into three groups: 1) those who had undergone Al-Hijama with drug therapy; 2) those who had Al-Hijama plus a salt nasal solution and an analgesic, when needed; and 3) those who were regularly treated with ordinary medicine. The groups were re-examined after three months of treatment. The results showed significant differences on the effects of cupping, based on the results of the clinical and the laboratory analyses (Eosinophil). Al-Hijama therapy was found to be effective, simple, affordable, acceptable, and safe, when used correctly.